[I] 'did write this Wyll with my own hand': Simulation and Dissimulation in Isabella Whitney's 'Wyll and Testament'. Issue 4 (1st December 2020) - Markidou, Vassiliki
Abstract: This article attempts for the first time to shed light on the politics of simulation and dissimulation in Isabella Whitney's 'Wyll and Testament'. It also argues that the poem both reflects its creator's awareness of the celebrated English historical and topographical narratives and deviates from them by crucially omitting a seminal part of London's history, namely its Troynovant tradition. In so doing, as well as by defining a paradoxical urban landscape, Whitney presents a tale not of the (mythic) founding of the English capital with its patriarchal and nation-building connotations, but of its (satiric) bequeathal by benevolent femininity, as such offering its reader a different angle from which to explore and interpret early modern London.